On the flow behavior of confined vortex-rings - Yeo, Beverley Kai Wen (Nanyang Technological University, 2021)
Vortex-ring interactions with various geometries tend to reveal rich and complex fluid dynamics by nature of the intricate interactions between their vorticities and the boundary layers along the geometries. Furthermore, even though they are a fundamental elementary flow, a more comprehensive understanding of vortex-rings will have applications in more canonical flow scenarios such as turbomachinery and biological applications. However, vortex-rings confined axisymmetrically have not been well-studied despite their prevalence in the human body, such as in the left ventricle of the heart or blood flow through aneurisms. Hence, the current project employed a combination of Unsteady Reynolds-Averaged Navier-Stokes (URANS) simulation and dye visualization experiments to calculate the wall shear stress and pressure induced on a cylindrical tube geometry by propagating vortex-rings. It was found that the wall shear stress was significantly higher for a vortex-ring-driven flow as compared to a typical pressure gradient-driven pipe flow. Results also show that the wall shear stress of the cylindrical tube geometry generally consisted of two parts, namely, a first component induced by the vortex-ring cores, and a second component induced by the boundary layer at the wall caused by the vortex-ring. The current project also provides flow visualizations of the formation, transition, and decay of vortex-rings under different confinement ratios, finding that for severely confined vortex-rings, the vortex-ring propagates more slowly with a smaller distance covered before decay. Overall, the results of the current project have important implications on the design of stents and valves for bioengineers as well as for those investigating flow in constricted arteries and aneurisms.